Tumor necrosis factor-alpha and interferon-gamma induce inflammasome-mediated corneal endothelial cell death. (June 2021) - Gomez, Angela; Serrano, Andres; Salero, Enrique; Tovar, Arianna; Amescua, Guillermo; Galor, Anat; Keane, Robert W.; de Rivero Vaccari, Juan Pablo; Sabater, Alfonso L.
Abstract: Purpose: Chronic corneal endothelial cell (CEC) loss results in corneal edema and vision loss in conditions such as pseudophakic bullous keratopathy (PBK), Fuchs' dystrophy, and corneal graft failure. Low CEC density has been associated with an elevation of intraocular pro-inflammatory cytokines such as tumor necrosis factor (TNF)-α and interferon (INF)-γ. These cytokines are capable of triggering pyroptosis, a programmed cell death mechanism mediated by the inflammasome, prompting the activation of the pro-inflammatory cytokine interleukin (IL)-1β, the perpetuation of inflammation, and subsequent damage of corneal endothelial tissue. Therefore, the purpose of this study was to determine the deleterious contribution of the inflammasome and pyroptosis to CEC loss. Methods: CECs from human donor corneas were treated e x vivo with TNF-α and IFN-γ for 48 h. Levels of caspase-1 and IL-1β were then assayed by ELISA, and the expression of caspase-1 and gasdermin-D (GSDM-D) were confirmed by immunofluorescence. Endothelial cell damage was analyzed by a lactate dehydrogenase (LDH) release assay, and oxidative stress was determined by measuring the levels of reactive oxygen species (ROS) in the culture media. Results: Inflammasome activation and oxidative stress were elevated in CECs following exposure to TNF-α and IFN-γ, which resulted in cell death by pyroptosis as determined by LDH release which was inhibited by the caspase-1 inhibitor Ac-YVAD-cmk. Conclusion: CEC death is induced by the pro-inflammatory cytokines TNF-α and IFN-γ, which contribute to inflammasome activation. Moreover, the inflammasome is a promising therapeutic target for the treatment of chronic CEC loss. Highlights: TNF-α and IFN-γ exacerbates inflammasome activation in corneal endothelial cells. TNF-α and IFN-γ upregulates caspase-1 and GSDM-D in corneal endothelial cells. Inflammation-mediated endothelial cell death is regulated by the inflammasome. Inflammasome activation was in part the result of ROS formation. Corneal endothelial pyroptosis is modulated by caspase-1 inhibition.